2018
DOI: 10.1007/s10557-018-6787-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antazoline on Electrophysiological Properties of Atrial Muscle and Conduction System of the Heart

Abstract: PurposeAntazoline is a first-generation antihistaminic agent with additional anticholinergic properties and antiarrhythmic potential. Recent data shows its high effectiveness in sinus rhythm restoration among patients with paroxysmal atrial fibrillation. The effect of antazoline on electrophysiological parameters of the heart in vivo has not yet been examined. The aim of this study was to evaluate changes in electrophysiological parameters of the heart muscle and conduction system as a response to increasing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 15 publications
(11 reference statements)
1
16
0
Order By: Relevance
“…5 Basic studies have suggested a multichannel mode of action resulting in, among others, changes in inter-and intraatrial conduction and prolongation of QRS and QT intervals without significant influence on atrio-ventricular node or accessory pathway effective refractory periods. [6][7][8][9] In human healthy volunteers, the terminal elimination half-life of antazoline was 2.29 hours with a mean residence time 3.45 hours. 7 In the same experiment, the antazoline administration resulted in a significant decrease in stroke volume-94.9 ± 21.8 vs 82.4 ± 19.6 mL (P < 0.05).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Basic studies have suggested a multichannel mode of action resulting in, among others, changes in inter-and intraatrial conduction and prolongation of QRS and QT intervals without significant influence on atrio-ventricular node or accessory pathway effective refractory periods. [6][7][8][9] In human healthy volunteers, the terminal elimination half-life of antazoline was 2.29 hours with a mean residence time 3.45 hours. 7 In the same experiment, the antazoline administration resulted in a significant decrease in stroke volume-94.9 ± 21.8 vs 82.4 ± 19.6 mL (P < 0.05).…”
Section: Introductionmentioning
confidence: 99%
“…Antazoline is a I generation antihistaminic drug with antifibrillatory properties . Basic studies have suggested a multichannel mode of action resulting in, among others, changes in inter‐ and intraatrial conduction and prolongation of QRS and QT intervals without significant influence on atrio‐ventricular node or accessory pathway effective refractory periods . In human healthy volunteers, the terminal elimination half‐life of antazoline was 2.29 hours with a mean residence time 3.45 hours .…”
Section: Introductionmentioning
confidence: 99%
“…Antazoline is a I generation antihistaminic drug displaying antiarrhythmic properties . Antazoline is administered intravenously in 50–100 mg boluses until conversion of AF to sinus occurs or up to a cumulative dose of 250–300 mg . In a single clinical study over healthy volunteers, after the injection of 100 mg of antazoline the drug concentration in plasma declined rapidly to 10% of baseline within half an hour.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed mechanism of antiarrhythmic properties of antazoline is not entirely clear but current data point to a multichannel mode of action involving sodium and potassium channels . Animal model studies report a significant increase of atrial and ventricular effective refractory periods (ERP) leading to a remarkable increase in atrial and ventricular postrepolarization refractoriness, an antiarrhythmic mechanism observed in amiodarone or quinidine …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation